COMMUNITY KNOWLEDGE, ATTITUDE, AND BEHAVIOR TOWARDS RABIES IN BANJAR BATUSARI, SANGEH VILLAGE, ABIANSEMAL DISTRICT, BADUNG REGENCY - I Gusti Ngurah Putu Krisnu Mahaputra; I Wayan Masa Tenaya; I Made Sukada (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Rabies is a zoonotic disease caused by the genus Lyssavirus of the Rhabdoviridae family which is very fatal. In Indonesia, rabies has infected 26 of the 34 existing provinces. Bali has tested positive for rabies since 2008. The government and the people of Bali have made efforts to control rabies by carrying out mass rabies vaccinations for dogs, eliminating dogs that are not owned, and conducting education about the dangers of rabies to the public. This study aims to determine the knowledge, attitudes and behaviour of the community towards rabies in Banjar Batusari, Sangeh Village, Abiansemal District, Badung Regency, Bali. Data collection in this study was carried out directly by going to the field to conduct surveys and interviews with the community. The number of heads of families in Banjar Batusari is 153 families. Data obtained from the results of interviews regarding aspects of knowledge, aspects of attitudes, and aspects of the behaviour of the dog keeping community were tabulated using Ms. Excel, the data were analysed descriptively and qualitatively and displayed in the form of tables or graphs. The results showed that 100% of the knowledge of the people in Banjar Batusari had a high level of knowledge. The attitude of the people of Banjar Batusari can be categorized as a 100% positive attitude towards rabies. For the level of behaviour of the Banjar Batusari community, it is classified as good behaviour at 68.8%. Thus, the knowledge, attitude and behaviour of the community is expected to control rabies in the research location so that rabies cases are very small and make it easier to carry out rabies prevention and control there.